Quinolines: microwave-assisted synthesis and their antifungal, anticancer and radical scavenger properties - Liberto, Natália Aparecida (2017)
An efficient method for the synthesis of quinolines using microwave irradiation was developed providing 28 quinolines with good yields. The reaction procedures are environmentally friendly, convenient, mild and of easy work-up. Quinolines were evaluated for their antifungal, anticancer and antioxidant properties and exhibited high activities in all tests performed.